2005
DOI: 10.1111/j.1460-9568.2005.03902.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionate receptor autoradiography in mouse brain after single and repeated withdrawal from diazepam

Abstract: Withdrawal from chronic treatment with benzodiazepines is associated with increased neuronal excitability leading to anxiety, aversive effects and increased seizure sensitivity. After repeated withdrawal experiences, seizure sensitivity increases while withdrawal-induced anxiety and aversion decrease. We used autoradiographical methods employing [(3)H]Ro48 8587, a selective ligand for glutamatergic alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors, to study withdrawal-induced changes in AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
2
2
1
Order By: Relevance
“…This may be apparent as the increase in hippocampal AMPA binding demonstrated and could result from the removal of GABAergic inhibition following drug withdrawal. This is further supported by recent mouse studies in our laboratories in which there was an increase in AMPA receptor binding in the hippocampus following a single withdrawal from chronic DZP (Allison et al, 2005). These data are also consistent with evidence of increased AMPA binding in the hippocampus 48 h following cessation of 7-day chronic treatment with high doses of flurazepam and increases in hippocampal AMPA receptormediated transmission and withdrawal anxiety 24 h following flurazepam withdrawal (Van Sickle et al, 2004).…”
Section: Hippocampussupporting
confidence: 78%
See 2 more Smart Citations
“…This may be apparent as the increase in hippocampal AMPA binding demonstrated and could result from the removal of GABAergic inhibition following drug withdrawal. This is further supported by recent mouse studies in our laboratories in which there was an increase in AMPA receptor binding in the hippocampus following a single withdrawal from chronic DZP (Allison et al, 2005). These data are also consistent with evidence of increased AMPA binding in the hippocampus 48 h following cessation of 7-day chronic treatment with high doses of flurazepam and increases in hippocampal AMPA receptormediated transmission and withdrawal anxiety 24 h following flurazepam withdrawal (Van Sickle et al, 2004).…”
Section: Hippocampussupporting
confidence: 78%
“…DZP group, a compensatory downregulation of the system may have taken place due to repeated withdrawals, such that [ 3 H]Ro48 8587 binding is now restored to control levels ( Figure 3). Consistent with these results, we have recently reported increases in AMPA receptor binding in these thalamic nuclei in mice experiencing a single withdrawal from chronic DZP (Allison et al, 2005).…”
Section: Thalamussupporting
confidence: 73%
See 1 more Smart Citation
“…Our results differ from other studies that find increases in GluR1 and GluR2B, but no increase in GluR2A mRNA levels in the hippocampus after diazepam treatment [118,119]. Increases in the expression of AMPA receptor subunit mRNAs and AMPA receptor ligand binding have been reported in a number of brain areas after BZ withdrawal [53,289]. We expected that Study 2 would identify increases in GluR1 and GluR2B mRNA, as found in other studies looking at repeated diazepam in mice [118,119].…”
Section: Nmdacontrasting
confidence: 99%
“…According to the published data (Dunworth and Stephens 1998 ; Becker et al 1998 ), glutamate neurotransmission is partially responsible for this process. Still, upregulation of transmission mediated via AMPA receptors did not seem to be very important in the enhanced seizure activity after diazepam repeated withdrawal, but intensified AMPA receptor binding in brain areas responsible for emotional responses and seizure activity has been seen in mice subjected to 21-day benzodiazepine treatment alone (Allison et al 2005 ). On the other hand, upregulation of the NMDA receptor seems to play an important role in the hypersusceptibility of the diazepam-withdrawn mice to seizure incidents (Tsuda et al 1998b ).…”
Section: Introductionmentioning
confidence: 99%